Burden of ischemic stroke attributable to high low-density lipoprotein cholesterol in China from the global burden of disease study 2021 - Hua Xue; Yuqi Zeng; Xinyang Zou; Yanhong Jiang; Wenhui Fan; Yongkun Li (Scientific Reports)
Abstract High low-density lipoprotein cholesterol are a significant risk factor for ischemic stroke. This study aims to analyze the burden of disease and temporal trends of ischemic stroke attributable to high LDL-C (IS-hLDL-C) in China, thereby providing a scientific basis for the development of effective prevention and intervention strategies. This study extracted the age-standardized mortality rates (ASMRs) and age-standardized disability-adjusted life years rates (ASDRs) of IS-hLDL-C from the global burden of disease (GBD) 2021. Stratified analysis was performed by gender and age groups. Joinpoint regression models were used to calculate average annual percentage changes (AAPC) to assess trends in IS-hLDL-C burden between 1990 and 2021. Age-period-cohort (APC) model to estimate the independent effects of age, period, and cohort on IS-hLDL-C burden. In 2021, the total number of IS-hLDL-C deaths in China was 300,052 (95% UI 92,515–527,456), and disability-adjusted life years (DALYs) was 6,850,565 (95% UI 2,313,203 − 11,418,167). From 1990 to 2021, ASMRs changed from 18.23 (95% CI 5.52–33.43) to 15.93 (95% CI 4.83–28.08), and the AAPC was −0.47 (95% CI −0.83 to −0.10). The ASDRs decreased from 385.65 (95% CI 129.83 to 647.51) in 1990 to 335.59 (95% CI 112.75 to 566.25) in 2021, with an AAPC of −0.49 (95% CI −0.83 to −0.10). Sex-stratified analysis showed that male had greater ASMRs and ASDRs than female. Age-stratified analysis showed that the burden was greatest among the elderly. In the age-period-cohort analysis, the age effect of IS-hLDL-C showed a continuous increasing trend during the study period. The period effect generally showed a positive trend during the study period. From 1990 to 2021, while the ASMRs and ASDRs related to IS-hLDL-C have decreased in China, the absolute numbers of deaths and DALYs remain substantial. The burden of IS-hLDL-C disease is disproportionately higher among male and the elderly. Given large population and the ongoing trend of population aging, it is essential to consider various lipid-lowering strategies in the future to allocate healthcare resources effectively and reduce the disease burden associated with IS-hLDL-C.